Tolerability of the COX-1/COX-2 inhibitor lornoxicam in the treatment of acute and rheumatic pain. (October 2016) - Parada, Luis; Marstein, Jens Pauli; Danilov, Andrey
Aim: To assess the safety of lornoxicam with particular focus on gastrointestinal (GI) events.Methods: Data on adverse drug reactions (ADRs) were pooled from 60 comparative studies of lornoxicam.Results: A total of 6420 patients received lornoxicam, 1192 received placebo and 3770 received a comparator analgesic. ADRs were reported by 21% of lornoxicam-treated patients, with GI events the most frequent (14 vs 8% with placebo). Across 15 studies that compared lornoxicam (n = 1287) with another NSAID (n = 1010), there was a reduced risk of a GI ADR with lornoxicam (0.78 [95% CI: 0.64–0.96]; p = 0.017).Conclusion: Lornoxicam was well tolerated with the type of GI events observed consistent with the known safety profile of NSAIDs.